Bridging Theory and Practice in Arabic Language Education - Hidayatullah, Ach Syarif; Fauji, Imam (Indonesian Journal of Islamic Studies, 2023)
This study examines the alignment of the textbook "Al-Iktisyaf" with the inductive method in Arabic language education, focusing on nahwu learning. Through qualitative analysis, including literature review and descriptive study methods, the research identifies strengths and weaknesses in the textbook's approach. While "Al-Iktisyaf" follows the sequence of the inductive method, it lacks emphasis on practical nahwu learning, particularly Wadhifah Nahwiyyah. The findings highlight the need for supplementary resources to enhance practical exercises and contemporary linguistic approaches in Arabic language education. Highlight: Method analysis: "Al-Iktisyaf" and inductive approach in Arabic language education. Practical learning: Strengths and weaknesses in functional nahwu instruction. Supplementary resources: Essential for enhancing practical exercises in Arabic language education. Keywoard: Arabic Language Education, Al-Iktisyaf Textbook, Inductive Method, Nahwu Learning, Supplementary Resources